Analytical advances in detection of performance-enhancing compounds - Bowers, L. D. (Clinical Chemistry, 1997)
The use and abuse of performance-enhancing substances has been an issue in sports since the ancient Greeks. The availability of numerous synthetic steroids and recombinant peptide hormones has made testing an analytical challenge. Recent advances in mass spectrometry have provided an opportunity to decrease detection limits. The Atlanta Olympic Games in 1996 marked the first time every specimen was screened by gas chromatography (GC) coupled to high-resolution mass spectrometry (MS). A further improvement may be seen with GC/MS/MS and quadrupole ion traps. Electrospray HPLC/MS has also been applied to the detection and confirmation of peptide hormones in urine. The ability to detect subtle differences in oligosaccharide structure may provide a way to detect abuse of recombinant glycoproteins. Simply decreasing detection limits is not enough; new technology also allows development of a foundation on which to base interpretation. Application of HPLC/MS/MS has allowed direct measurement of steroid conjugates in urine. The relative importance of sulfate, glucuronide, and other conjugates and metabolites of testosterone and epitestosterone can now be assessed. In the international sports arena, the impact of genetic metabolic disposition must also be considered if we are to provide an equitable system. Further research will establish more-refined criteria for the detection threshold of abused substances.